Ankylosing spondylitis: acute/subacute vs. chronic iridocyclitis - a bidirectional two-sample Mendelian randomization study - Li, Hui; Xu, Yingying; Guo, Qin; Zhang, Tiantian; Zhou, Shufen; Wu, Meimei; Cheng, Yuanxiong; Guo, Chengshan (Frontiers in Immunology, 2024)
Background: Observational studies found associations between ankylosing spondylitis (AS) and iridocyclitis (IC), but the causality remained unconfirmed. Methods: We employed two-sample Mendelian randomization (MR) to investigate the bidirectional causal relationships between AS and IC. Single-nucleotide polymorphisms (SNPs) were chosen from the FinnGen database's genome-wide association studies (GWAS) following a rigorous evaluation of the studies' quality. Sensitivity analysis was performed to assess the potential influence of pleiotropy and heterogeneity on the MR findings. Results: Elevated genetic risk for AS showed positive causal effects on IC and its subtypes (IC, OR = 1.094, 95% CI = 1.035-1.157, P = 0.00156; Acute/Subacute IC, OR = 1.327, 95% CI = 1.266-1.392, P = 8.73×10-32; Chronic IC, OR = 1.454, 95% CI = 1.308-1.618, P = 5.19×10-12). Significant causal association was specifically observed between Acute/Subacute IC and AS (OR = 2.107, 95% CI = 1.435-3.094, P = 1.43×10-4). Sensitivity analysis suggested that horizontal pleiotropy was unlikely to influence the causality, and the leave-one-out analysis confirmed that a single SNP did not drive the observed associations. Conclusion: Our findings provide new proof of a positive causal relationship between AS and IC in the European population. Notably, it is Acute/Subacute IC, rather than IC as a whole or Chronic IC, that is associated with an elevated risk of AS. These results emphasize the significance of considering AS characteristics in the diagnosis of Acute/Subacute IC.